Tradisi Budaya Intar Terang dalam Pernikahan Masyarakat Way Kanan Adat Lampung Pepadun - Chairunisa Mardiah Ramadhani (Insan Cendekia : Jurnal Pendidikan dan Kebudayaan, 2024)
The focus of this research study is the traditional Lampung marriage.The purpose of the research titled "The Pattern of Isam in the Intar Terang Tradition in the Lampung Pepadun Way Kanan Marriage" is to describe the Lampung Pepadun community and the intar terang tradition.Intar Terang is a way of releasing and handing over a daughter to a bachelor family during the day.The many Islamic values contained in this marriage tradition are the reason why many Pepadun in Lampung still marry according to their local customs.The influence of Islam in the Pepadun marriage customs of Lampung does not erase the original identity of Lampung culture, but rather enriches the local culture.The data source comes from an interview with one of the community members who has been designated as an informant and uses qualitative descriptive analysis methods.The purpose of the Intar Padang ceremony is to introduce the groom to the bride's close relatives, specifically, and generally to the community in the neighborhood.